Sudden Shift to English Online Learning: Nursing Students’ Anxiety Levels - Santa Maya Pramusita; Komilie Situmorang; Dwi Yulianto Nugroho (Linguistic, English Education and Art (LEEA) Journal, 2022)
COVID-19 pandemic has forced educational institutions in Indonesia to convert face-to-face learning into online learning. This sudden change certainly brings many challenges, one of which is related to students’ anxiety. This research aims to identify the anxiety level of nursing students at Pelita Harapan University while learning English virtually. Quantitative method was applied, with a Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire as an instrument. Second year nursing students who had passed the English for Nurses course were the population of this study. To generate the sample, the researchers utilized convenience sampling technique, resulting in 182 respondents. The results showed that 69.8% of respondents felt moderately anxious during the English online class. In addition, test anxiety was the most common anxiety category experienced by nursing students. It made students afraid of failing to get good grades, being overwhelmed in understanding the material, nervous when they must speak English, and panicking when they do not comprehend the oral feedback given by the teacher in synchronous class. The results of this study are expected to provide insight to educators to develop strategies to reduce students' anxiety levels. Keywords: Anxiety, English, Nursing, Pandemic